POTATO PHYTONEMATODES OF SAMARKAND REGION (Proceedings of International Educators Conference, 2023)
The article presents information about potato phytonematodes of Samarkand region. Nematodes were observed to be more common in the soil around the roots of potato crops than in the roots, stems and leaves. In the fauna of potato phytonematodes grown in different regions, species groups belonging to a certain region and species groups common to all studied regions were identified. Plant parasitic nematodes - Bitylenchus dubius, Rotylenchus goodeyi, Helicotylenchus erythrinae, H. multicinctus, Pratylenchus pratensis, P. macrophallus and Ditylenchus dipsaci species were found.